2015
DOI: 10.1111/resp.12475
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood and bronchial submucosal eosinophilia and reticular basement membrane thickening in chronic obstructive pulmonary disease

Abstract: A sputum eosinophilia is observed in 10–40% of COPD subjects. The blood eosinophil count is a biomarker of sputum eosinophilia, but whether it is associated with bronchial submucosal eosinophils is unclear. In 20 COPD subjects and 21 controls we assessed the number of bronchial submucosal eosinophils and reticular basement membrane thickening and found these were positively correlated with the blood eosinophil percentage. In COPD, blood eosinophils are a good biomarker of bronchial eosinophilia and remodelling. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 7 publications
1
52
0
1
Order By: Relevance
“…Another important aspect that also reflects the discrepancies is whether the BEC is a good reference of the eosinophils in the airway. Thus, in a study comparing the BEC with the eosinophilia in the bronchial submucosa, a good correlation is obtained between both determinations in patients with COPD . Another study conducted in Australia comparing the BEC with the eosinophils in sputum also obtained a good correlation between both compartments .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Another important aspect that also reflects the discrepancies is whether the BEC is a good reference of the eosinophils in the airway. Thus, in a study comparing the BEC with the eosinophilia in the bronchial submucosa, a good correlation is obtained between both determinations in patients with COPD . Another study conducted in Australia comparing the BEC with the eosinophils in sputum also obtained a good correlation between both compartments .…”
Section: Discussionmentioning
confidence: 84%
“…Thus, in a study comparing the BEC with the eosinophilia in the bronchial submucosa, a good correlation is obtained between both determinations in patients with COPD. 33 Another study conducted in Australia comparing the BEC with the eosinophils in sputum also obtained a good correlation between both compartments. 24 On analysing a population with COPD that presents with exacerbations, the BEC would be the better indicator of eosinophilia in sputum.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 81%
“…Eltboli and colleagues [24] reported that there is a strong correlation between peripheral blood and bronchial eosinophils and reticular basement membrane thickening and suggested that the peripheral blood eosinophil count does identify COPD subjects with a greater tissue eosinophilia. A recent study documented that airway wall thickness is independently associated with a stronger decline in lung function [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although blood eosinophils are easy to measure in clinical practice, it is uncertain whether they closely reflect sputum or tissue eosinophilia. Increased blood eosinophils predict an increase in sputum eosinophils (>3%) in around 70% of patients but there is only a weak relationship between blood and sputum or bronchial eosinophils in COPD patients . One problem is that blood eosinophils counts are variable over time and even within the same day, so that it is important to make repeated measurements.…”
Section: Eosinophilic Copdmentioning
confidence: 99%